High-restoring-force shape memory polyurethane material based on Ag-S coordination and preparation method of high-restoring-force shape memory polyurethane material

By introducing Ag-S coordination and disulfide bonds into polyurethane materials, a multi-stage dynamic network structure is constructed, which solves the problems of low recovery stress and inreconstructibility of existing shape memory polymer materials, and achieves high recovery stress and can The effect of recycled recycling.

CN119463106AInactive Publication Date: 2025-02-18SHANGHAI JIAOTONG UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411591651.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing shape memory polymer materials have low recovery stress and cannot be reconstructed under external stimulation, which limits their use in a wider field. At the same time, due to the irreversibility of chemical crosslinking, the material is difficult to reprocess and reuse, resulting in an environment. pressure.

Method used

By introducing Ag-S coordination into polyurethane materials, a multi-stage dynamic network structure is constructed, combining disulfide bond synergy, the recovery stress and tensile strength of the material are improved, and recyclable recycling and remote infrared drive are realized.

Benefits of technology

It realizes high stress recovery, excellent tensile strength, repeatable recycling and remote infrared-driven shape memory polyurethane material, which improves the mechanical properties and shape memory properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463106A_ABST
    Figure CN119463106A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polymer composite materials and intelligent polymer materials, in particular to a high-restoring-force shape memory polyurethane material based on Ag-S coordination and a preparation method of the high-restoring-force shape memory polyurethane material. A multi-stage dynamic network structure is formed in the polyurethane material, and the multi-stage dynamic network structure comprises an Ag-S coordination bond and a silver nanoparticle monomer. The multi-stage dynamic network structure further comprises disulfide bonds, PCL (Polycaprolactone) and PEG (Polyethylene Glycol) chain segments. Comprising the following raw materials in percentage by mass: 60-80 wt% of a semi-crystalline compound, 5-10 wt% of isocyanate, 5-10 wt% of a chain extender, 5-10 wt% of a cross-linking agent and 0.5-5 wt% of silver nitrate. Compared with the prior art, the method has the advantages that the multi-stage dynamic network structure is constructed through in-situ reduction of the silver nanoparticles in the system by utilizing the silver-sulfur coordination effect, and the mechanical property and the shape memory property of the composite material are remarkably improved on the premise that the composite material still has the recycling capacity and the permanent shape programmability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer composite materials and intelligent polymer materials, in particular to a high-restoration shape memory polyurethane material based on Ag-S coordination and a preparation method thereof. Background Art

[0002] In the face of the rise of various new application fields, such as spatial unfolding structures, biomedical smart sutures, deformable flexible electronic components and soft robots, shape memory polymer materials (SMP) have attracted widespread attention due to their excellent mechanical properties, rapid response capabilities and potential self-healing properties. SMP can restore the temporary deformed state to the initial undeformed state after applying external stimuli (such as heat or light). For example, semi-crystalline shape memory polymers, when the polymer is in a temporary deformed state, the crystalline region in the molecular segment melts under temperature stimulation, and the network nodes (such as chemical crosslinking or topological entanglement, etc.) will pull the segment back to the initial state. However, most SMPs generally have problems such as low recovery stress and non-reconstruction of the initial state, which limits their use in a wider range of fields. It is generally believed that the recovery stress generated when SMP returns to the initial state under external stimulation is determined by the entropy energy stored in the polymer network, and the stored entropy energy is closely related to the density and strength of the network nodes. A high degree of chemical cross-linking can increase the network node density in the system, thereby further improving the recovery stress of SMP. However, the irreversibility of chemical cross-linking makes it difficult to reprocess and reuse the material. The large amount of difficult-to-degrade waste generated after use has brought tremendous pressure to the environment.

[0003] Vitrimer is a new type of material. The covalent adaptive network (CAN) in the molecular network will undergo dynamic covalent bond exchange under external stimulation (such as heat, light and force), inducing dynamic adjustment of the material polymer network structure. When the stimulation is eliminated, the dynamic covalent bond polymer can show high stability like general covalent polymers. This property provides the possibility for the recycling and reprocessing of materials. More importantly, through the bond exchange of the cross-linked structure, conditions are created for the reconstruction of the initial state of SMP. The topological rearrangement of the polymer network can be induced mainly by the dynamic covalent bonds in the network, including disulfide bonds, borate bonds, transcarbamylation and ester exchange. However, it is worth noting that the lower bond energy of dynamic covalent bonds such as disulfide bonds makes the strength and recovery stress of SMP containing this type of vitrimer too low. The contradiction between the demand for high recovery stress and large recoverable strain and the recyclability of materials restricts the further development and application of SMP.

[0004] Application No. CN109912773A discloses a method for preparing a shape memory polyurethane synthesized from polycaprolactone, polyethylene glycol, diisocyanate, helical non-planar and planar chain extenders. The elongation at break of the polymer material is 500-600%, the tensile strength is 15-20MPa, and the thermal decomposition temperature is 280-320°C. However, its preparation method is relatively cumbersome and requires the application of microwave reaction and other methods. Moreover, due to the lack of dynamic covalent bonds, it cannot be repeatedly recycled, which limits its practical application. Application No. CN113845643A discloses a method for preparing a shape memory polyurethane synthesized from a poly-ε-caprolactone (PCL-Se-Se-PCL) macromolecular diol containing a diselenide structure and a saturated aliphatic diisocyanate. The polymer material has good biocompatibility, shape memory function and self-healing function. The diselenide bond structure contained in PCLU-Se-Se-PCLU can provide excellent redox dual responsiveness, but its preparation method is relatively cumbersome. Although it has self-healing recovery performance, it does not consider problems such as shape memory recovery stress, which limits its application in a wider field. Application No. CN113583208A discloses a polycaprolactone-based polymer electrolyte containing a disulfide bond and having both self-repair and shape memory properties. The disulfide-containing polyurethane prepolymer is mixed with an alkali metal salt and then cross-linked by a multi-arm cross-linking agent to obtain a polymer with both self-repair and shape memory functions. The main application scenario is polymer electrolytes. It realizes the self-repair function through a disulfide bond, but due to the weak bond energy of dynamic covalent bonds such as disulfide bonds, the overall mechanical properties of the material are poor.

[0005] Therefore, it is of great significance to provide a shape memory polyurethane elastomer that has high recovery stress, large recoverable strain and repeatable recycling. This material has great application potential in soft robots and actuators. Summary of the invention

[0006] The present invention overcomes the deficiencies of the prior art and provides a high-restoration shape memory polyurethane material based on Ag-S coordination and a preparation method thereof. The Ag-S coordination effect is introduced into the system to improve the dynamic covalent bond, and the Ag-S coordination effect is synergistic with the disulfide bond to construct a multi-level dynamic network structure, so that the material has the characteristics of high recovery stress, excellent tensile strength, repeatable recycling and remote infrared drive.

[0007] To achieve the above objectives, a high-resilience shape memory polyurethane material based on Ag-S coordination is designed. A multi-level dynamic network structure is formed in the polyurethane material, which includes Ag-S coordination bonds and silver nanoparticle monomers.

[0008] The multi-level dynamic network structure also includes disulfide bonds, PCL and PEG segments.

[0009] The polyurethane material comprises the following raw materials in mass fractions: 60-80wt% of a semi-crystalline compound, 5-10wt% of an isocyanate, 5-10wt% of a chain extender, 5-10wt% of a cross-linking agent, and 0.5 to 5wt% of silver nitrate.

[0010] The semi-crystalline compound includes at least one of polycaprolactone diol, polyethylene glycol, and polytetramethylene glycol; the isocyanate includes at least one of hexamethylene diisocyanate, isophorone diisocyanate, and diphenylmethane diisocyanate; the chain extender includes at least one of 4,4'-diaminodiphenyl disulfide, bis(4-hydroxyphenyl) disulfide, and 2-hydroxyethyl disulfide; and the cross-linking agent is a polyol cross-linking agent, including at least one of triethanolamine, glycerol, and N,N,N',N'-tetrakis(2-hydroxypropyl)ethylenediamine.

[0011] The method also includes the following raw materials in mass fractions: 0.1-0.5wt% of a catalyst and a solvent with a total solid content of 100%-200%; the catalyst includes at least one of dibutyltin dilaurate, stannous octoate and stannous oleate, and the solvent is N,N-dimethylformamide.

[0012] To achieve the above purpose, a preparation method of a high-restoration shape memory polyurethane material based on Ag-S coordination is designed, comprising the following steps: S1, dispersing a semi-crystalline compound and an isocyanate, mixing them with a solvent and reacting them to obtain a polyurethane prepolymer 1; S2, mixing a chain extender, a crosslinking agent and a solvent, and then adding the polyurethane prepolymer 1 and a catalyst to react to obtain a polyurethane prepolymer 2 containing a disulfide bond; S3, mixing silver nitrate with a solvent to obtain a functional filler, wherein free silver ions in the functional filler are reduced to silver nanoparticle monomers; S4, mixing the polyurethane prepolymer 2 with the functional filler, stirring and injection molding after mixing, and a part of the silver nanoparticle monomer reacts with the disulfide bond to form an Ag-S coordination bond.

[0013] Before the step S1, the semi-crystalline compound is dried at a temperature of 75-85° C. for 6-12 h.

[0014] In the step S1, the mixing reaction time is 10-40 min; in the step S2, the polyurethane prepolymer 1 reacts with the chain extender and the crosslinking agent for 10-40 min; in the step S3, silver nitrate and a catalyst are added to the polyurethane prepolymer 2 solution, and the reaction time is continued for 5-30 min; the reaction processes of the steps S1 to S3 are all carried out under nitrogen protection, and the reaction temperature is 60-80°C.

[0015] In the step S2, the molar ratio of the chain extender to the cross-linking agent is 1-5:7-2.

[0016] The injection molding method in step S3 is as follows: injecting the obtained cross-linking reaction solution into a polytetrafluoroethylene mold, and curing it at 80° C. for 48 to 72 hours to synthesize a polyurethane film.

[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. Through the in-situ reduction of silver nanoparticles in the system, a multi-level dynamic network structure is constructed using the silver-sulfur coordination effect. Under the premise that the composite material still has the ability to be recycled and permanent shape programmable, the mechanical properties and shape memory properties of the composite material are significantly improved.

[0018] 2. Due to the presence of in-situ reduced silver nanoparticles in the system, their excellent photothermal properties can enable the shape memory material of this patent to have the ability to be remotely driven by infrared light. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a process flow chart of the present invention.

[0020] Figure 2 The infrared spectra and Raman spectra of the polyurethane materials obtained in Examples 1-4 of the present invention and Comparative Example 1 are shown.

[0021] Figure 3 This is an x-ray photoelectron spectrum curve of the polyurethane material obtained in Example 2 of the present invention.

[0022] Figure 4 It is a DSC test curve diagram of the polyurethane materials obtained in Examples 1-4 of the present invention and Comparative Example 1.

[0023] Figure 5 It is a tensile curve diagram of the polyurethane materials obtained in Examples 1-4 of the present invention and Comparative Example 1.

[0024] Figure 6 This is a DMA curve diagram of the polyurethane material obtained in Example 2 of the present invention.

[0025] Figure 7 This is a tensile curve diagram of the polyurethane material obtained in Example 2 of the present invention after repeated recycling. DETAILED DESCRIPTION

[0026] The present invention will be further described below with reference to the accompanying drawings. Embodiment 1

[0027] This embodiment prepares a shape memory polyurethane elastomer, and the specific steps are as follows: 16 g of polycaprolactone diol (PCL-diOH) with a molecular weight of 20,000 and 4 g of polyethylene glycol (PEG) with a molecular weight of 2,000 were weighed in a predetermined ratio of 8:2. After vacuum drying at 80 °C for 6 h, 40 ml of N,N-dimethylformamide (DMF) was added and stirred at 80 °C until dissolved. After the solution was clarified, 3 g of hexamethylene diisocyanate (HDI) was added and vacuum stirred for 20 minutes to start prepolymerization. At the same time, 0.75 g of N,N,N',N'-tetrakis (2-hydroxypropyl) ethylenediamine (HPED), 0.18 g of triethanolamine (TEA), and 1.08 g of 2-hydroxyethyl disulfide (HEDS) were weighed and dissolved in 10 ml of DMF. The two solutions were mixed at 80 °C, 20 μL of DBTDL catalyst was added, and polymerization was promoted under vacuum for 20 min. Next, 0.1 g of silver nitrate (AgNO3) was dissolved in 10 ml of DMF and added to the mixed solution. After stirring for 20 min under vacuum, the final solution was transferred to a polytetrafluoroethylene mold.

[0028] This embodiment uses completely dry DMF solvent. Embodiment 2

[0029] 16 g of polycaprolactone diol (PCL-diOH) with a molecular weight of 20,000 and 4 g of polyethylene glycol (PEG) with a molecular weight of 2,000 were weighed in a predetermined ratio of 8:2. After vacuum drying at 80 °C for 6 h, 40 ml of N,N-dimethylformamide (DMF) was added and stirred at 80 °C until dissolved. After the solution was clarified, 3 g of hexamethylene diisocyanate (HDI) was added and vacuum stirred for 20 minutes to start prepolymerization. At the same time, 0.75 g of N,N,N',N'-tetrakis (2-hydroxypropyl) ethylenediamine (HPED), 0.18 g of triethanolamine (TEA), and 1.08 g of 2-hydroxyethyl disulfide (HEDS) were weighed and dissolved in 10 ml of DMF. The two solutions were mixed at 80 °C, 20 μL of DBTDL catalyst was added, and polymerization was promoted under vacuum for 20 min. Next, 0.126 g of silver nitrate (AgNO3) was dissolved in 10 ml of DMF and added to the mixed solution. After stirring for 20 min under vacuum, the final solution was transferred to a polytetrafluoroethylene mold.

[0030] This embodiment uses completely dry DMF solvent. Embodiment 3

[0031] 16 g of polycaprolactone diol (PCL-diOH) with a molecular weight of 20,000 and 4 g of polyethylene glycol (PEG) with a molecular weight of 2,000 were weighed in a predetermined ratio of 8:2. After vacuum drying at 80 °C for 6 h, 40 ml of N,N-dimethylformamide (DMF) was added and stirred at 80 °C until dissolved. After the solution was clarified, 3 g of hexamethylene diisocyanate (HDI) was added and vacuum stirred for 20 minutes to start prepolymerization. At the same time, 0.75 g of N,N,N',N'-tetrakis (2-hydroxypropyl) ethylenediamine (HPED), 0.18 g of triethanolamine (TEA), and 1.08 g of 2-hydroxyethyl disulfide (HEDS) were weighed and dissolved in 10 ml of DMF. The two solutions were mixed at 80 °C, 20 μL of DBTDL catalyst was added, and polymerization was promoted under vacuum for 20 min. Next, 0.252 g of silver nitrate (AgNO3) was dissolved in 10 ml of DMF and added to the mixed solution. After stirring under vacuum for 20 min, the final solution was transferred to a polytetrafluoroethylene mold.

[0032] This embodiment uses completely dry DMF solvent. Embodiment 4

[0033] 16 g of polycaprolactone diol (PCL-diOH) with a molecular weight of 20,000 and 4 g of polyethylene glycol (PEG) with a molecular weight of 2,000 were weighed in a predetermined ratio of 8:2. After vacuum drying at 80 °C for 6 h, 40 ml of N,N-dimethylformamide (DMF) was added and stirred at 80 °C until dissolved. After the solution was clarified, 3 g of hexamethylene diisocyanate (HDI) was added and vacuum stirred for 20 minutes to start prepolymerization. At the same time, 0.75 g of N,N,N',N'-tetrakis (2-hydroxypropyl) ethylenediamine (HPED), 0.18 g of triethanolamine (TEA), and 1.08 g of 2-hydroxyethyl disulfide (HEDS) were weighed and dissolved in 10 ml of DMF. The two solutions were mixed at 80 °C, 20 μL of DBTDL catalyst was added, and polymerization was promoted under vacuum for 20 min. Next, 0.504 g of silver nitrate (AgNO3) was dissolved in 10 ml of DMF and added to the mixed solution. After stirring for 20 min under vacuum, the final solution was transferred to a polytetrafluoroethylene mold.

[0034] This embodiment uses completely dry DMF solvent.

[0035] Comparative Example 1 16 g of polycaprolactone diol (PCL-diOH) with a molecular weight of 20,000 and 4 g of polyethylene glycol (PEG) with a molecular weight of 2,000 were weighed in a predetermined ratio of 8:2. After vacuum drying at 80 °C for 6 h, 40 ml of N,N-dimethylformamide (DMF) was added and stirred at 80 °C until dissolved. After the solution was clarified, 3 g of hexamethylene diisocyanate (HDI) was added and vacuum stirred for 20 minutes to start prepolymerization. At the same time, 0.75 g of N,N,N',N'-tetrakis (2-hydroxypropyl) ethylenediamine (HPED), 0.18 g of triethanolamine (TEA), and 1.08 g of 2-hydroxyethyl disulfide (HEDS) were weighed and dissolved in 10 ml of DMF. The two solutions were mixed at 80 °C, and 20 μL of DBTDL catalyst was added to promote polymerization under vacuum for 20 min. The final solution was transferred to a polytetrafluoroethylene mold.

[0036] This embodiment uses completely dry DMF solvent.

[0037] Figure 2 The infrared spectra and Raman spectra of the polyurethane materials obtained in Examples 1-4 and Comparative Example 1 show that the peaks at 2935 and 2861 cm -1 The double peaks at 1722 and 1241 cm correspond to the symmetric and asymmetric vibration absorption peaks of -CH2-. -1 The absorption peaks at 2250–2270 cm-1 are derived from the carbonyl group of the PCL-diOH component and the ether bond of the PEG component, respectively, while the disappearance of the characteristic peak of –NCO, which should be at 2250–2270 cm-1, together proves the completion of the polymerization reaction. It can be found that there is no obvious difference between the spectra of the embodiment and the comparative example, indicating that the addition of silver nitrate does not interfere with the synthesis of polyurethane. Raman spectroscopy can further confirm the structure of polyurethane. As shown in the figure, all samples have a peak at 510 cm-1. −1 642 cm −1 There are two obvious peaks, which are attributed to the stretching vibration of SS and CS bonds. Therefore, the present invention successfully introduces disulfide bonds into the polyurethane system by using HEDS chain extender. This dynamic covalent bond dominates the repair and reconstruction of the molecular network.

[0038] Figure 3 The X-ray photoelectron spectrum curve of the polyurethane material obtained in Example 2 further verifies that the free silver ions in the system are reduced to silver nanoparticle monomers AgNPs by the DMF solvent. Figure 2As shown, the broadband scanning spectrum of the prepared sample shows peaks corresponding to C 1s (72.27 atomic %), O 1s (24.84 atomic %), N 1s (2.39 atomic %), S2p (0.38 atomic %) and Ag 3d (0.12 atomic %). Among them, the Ag 3d XPS spectrum of Example 2 has two peaks at 373.9 and 367.9 eV, corresponding to Ag 3d3 / 2 and Ag 3d5 / 2, respectively, with a spin energy separation of about 6 eV, confirming that silver exists in the system in the form of a single substance. In addition, the high-resolution S 2p spectrum of Example 2 is deconvoluted into four clear peaks. The fitting peaks near 164.9 eV and 163.8 eV correspond to S 2p1 / 2 and S 2p3 / 2, which belong to disulfide bonds, while the fitting peaks near 161.6 eV and 162.7 eV are in good agreement with the CS bond binding energy, which further verifies the existence of disulfide bonds in the multi-level dynamic network structure of polyurethane materials.

[0039] Figure 4 The DSC test curves of the polyurethane materials obtained in Examples 1-4 and Comparative Example 1 are shown. As shown in the figure, it can be found that the loading of silver nanoparticle monomer AgNPs will slightly increase the phase transition temperature, the crystallization temperature (Tc) gradually increases from 17.9°C to 20.5°C, and the crystalline melting temperature (Tm) gradually increases from 56.6°C to 58.1°C. This is because the Ag-S coordination bond formed by the silver nanoparticle monomer AgNPs and the disulfide bond enhances the intermolecular force, increases the mutual attraction between the molecular chains, and requires more heat to overcome these forces so that the molecular chains can move relatively freely, resulting in an increase in the phase transition temperature. But on the other hand, as nano-sized metal particles, silver nanoparticle monomer AgNPs have good thermal conductivity, and their uniform distribution in the matrix can make the composite heated evenly and more easily reach the phase transition temperature. Under the combined effect of these two factors, as the loading of silver nanoparticle monomer AgNPs increases, the Tc and Tm of the composite increase less.

[0040] Figure 5The tensile curves of the polyurethane materials obtained in Examples 1-4 and Comparative Example 1. It can be observed that the mechanical properties of SMP can be significantly improved by loading a small amount of silver nanoparticle monomers AgNPs, wherein the sample in Example 2 exhibits the best tensile properties (not only exhibiting a tensile strength of 25.93MPa, but also having an ultra-high strain of 1467.63%), which are 1.6 times and 1.3 times that of the sample in Comparative Example 1, respectively. This phenomenon is due to the fact that the silver nanoparticle monomers AgNPs reduced in situ in the system form dense coordination bonds with disulfide bonds, and this additional coordination bond can significantly increase the interaction force between polymer molecules. On the other hand, under the action of external force, stress concentration is easily generated at the junction of the hard segment and the crystal segment, thereby inducing the fracture of the polyurethane, and the uniformly distributed AgNPs can weaken the stress concentration effect in the system, thereby greatly improving the tensile strength of the composite material system. At the same time, we noticed that all samples had very good fracture strain. This is because the PEG soft segment was added to the system, which has a lower melting point and makes the molecular chain segments easier to move at room temperature, thus achieving ultra-high strain of the material.

[0041] Figure 6 This is the DMA curve of the polyurethane material obtained in Example 2. As shown in the figure, Example 2 obtains strain by heating and applying a certain external stress (0.15MPa). At this time, the temperature drops to 0°C, and the crystallization of PCL and PEG segments fixes the shape of the material. And after calculation, the shape fixation rate Rf is about 99.36% at this time. Subsequently, when the temperature is raised to above Tm, the crystalline region melts, the stored energy is rapidly released, and the shape is restored under the traction effect of the molecular segments. It is calculated that in the first shape memory cycle, another important parameter of SMP, the shape recovery rate Rr, is about 100%, which together proves the excellent shape memory effect of Example 2. In the three complete cycles recorded, Rf is maintained above 99%, which is due to the excellent crystallinity of the material, and multiple cycles can still perfectly realize the storage of internal stress. Rr decays to 96.18% in the second cycle and maintains a similar level (97.87%) in the third cycle.

[0042] Figure 7This is the tensile curve of the polyurethane material obtained in Example 2 after repeated recycling. A large number of disulfide bonds in the molecular chain of Example 2 break and regenerate at a suitable temperature, so that the material exhibits good recycling ability. The sample of Example 2 was chopped up, redissolved in DMF solvent at 90°C, and then a small amount of HDI was added, and it was placed in the mold again for curing to obtain a recycled sample. Subsequently, a tensile test was carried out on the cured recycled sample to further evaluate its reprocessing ability. Although the sample was re-cured, the mechanical properties of the PU-0.01Ag recycled sample still decreased to a certain extent. The tensile strength decreased from 25.93 MPa to 12.88 MPa, and the elongation at break also decreased from 1467% to 855%. This may be due to the breaking of some irreversible bonds during the recycling process, which led to a decrease in mechanical properties after recycling.

Claims

1. High-resilience shape memory polyurethane material based on Ag-S coordination, characterized by: A multi-level dynamic network structure is formed in the polyurethane material, and the multi-level dynamic network structure includes Ag-S coordination bonds and silver nanoparticle monomers.

2. The high-restoration shape memory polyurethane material based on Ag-S coordination according to claim 1, characterized in that: The multi-level dynamic network structure also includes disulfide bonds, PCL and PEG segments.

3. The high-restoration shape memory polyurethane material based on Ag-S coordination according to claim 1, characterized in that: The polyurethane material comprises the following raw materials in mass fractions: 60-80wt% of a semi-crystalline compound, 5-10wt% of an isocyanate, 5-10wt% of a chain extender, 5-10wt% of a cross-linking agent, and 0.5 to 5wt% of silver nitrate.

4. The high-restoration shape memory polyurethane material based on Ag-S coordination according to claim 3, characterized in that: The semi-crystalline compound includes at least one of polycaprolactone diol, polyethylene glycol, and polytetramethylene glycol; the isocyanate includes at least one of hexamethylene diisocyanate, isophorone diisocyanate, and diphenylmethane diisocyanate; the chain extender includes at least one of 4,4'-diaminodiphenyl disulfide, bis(4-hydroxyphenyl) disulfide, and 2-hydroxyethyl disulfide; and the cross-linking agent is a polyol cross-linking agent, including at least one of triethanolamine, glycerol, and N,N,N',N'-tetrakis(2-hydroxypropyl)ethylenediamine.

5. The high-restoration shape memory polyurethane material based on Ag-S coordination according to claim 3, characterized in that: The method also includes the following raw materials in mass fractions: 0.1-0.5wt% of a catalyst and a solvent with a total solid content of 100%-200%; the catalyst includes at least one of dibutyltin dilaurate, stannous octoate and stannous oleate, and the solvent is N,N-dimethylformamide.

6. A method for preparing a high-restoration shape memory polyurethane material based on Ag-S coordination, characterized in that: The steps include: S1, dispersing a semi-crystalline compound and an isocyanate, mixing them with a solvent and reacting them to obtain a polyurethane prepolymer 1; S2, mixing a chain extender, a crosslinking agent and a solvent, and then adding the polyurethane prepolymer 1 and a catalyst to react to obtain a polyurethane prepolymer 2 containing a disulfide bond; S3, mixing silver nitrate with a solvent to obtain a functional filler, wherein free silver ions in the functional filler are reduced to silver nanoparticle monomers; S4, mixing the polyurethane prepolymer 2 with the functional filler, stirring and injection molding after mixing, and a part of the silver nanoparticle monomer reacts with the disulfide bond to form an Ag-S coordination bond.

7. The method for preparing a high-restoration shape memory polyurethane material based on Ag-S coordination according to claim 6, characterized in that: Before the step S1, the semi-crystalline compound is dried at a temperature of 75-85° C. for 6-12 h.

8. The method for preparing a high-restoration shape memory polyurethane material based on Ag-S coordination according to claim 6, characterized in that: In the step S1, the mixing reaction time is 10-40 min; in the step S2, the polyurethane prepolymer 1 reacts with the chain extender and the crosslinking agent for 10-40 min; in the step S3, silver nitrate and a catalyst are added to the polyurethane prepolymer 2 solution, and the reaction time is continued for 5-30 min; the reaction processes of the steps S1 to S3 are all carried out under nitrogen protection, and the reaction temperature is 60-80°C.

9. The method for preparing a high-restoration shape memory polyurethane material based on Ag-S coordination according to claim 6, characterized in that: In the step S2, the molar ratio of the chain extender to the cross-linking agent is 1-5:7-2.

10. The method for preparing a high-restoration shape memory polyurethane material based on Ag-S coordination according to claim 6, characterized in that: The injection molding method in step S3 is as follows: injecting the obtained cross-linking reaction solution into a polytetrafluoroethylene mold, and curing it at 80° C. for 48 to 72 hours to synthesize a polyurethane film.

Citation Information

Patent Citations

  • Shape memorizing polyurethane and preparation method thereof

    CN109912773A

  • Shape memory polyurethane material with active oxygen responsiveness and anti-adhesion double functions

    CN113845643A

  • Preparation method of high-strength photoresponse self-repairing nano-composite polyurethane film

    CN112898611A

  • Polycaprolactone-based polymer electrolyte with self-repairing and shape memory characteristics and preparation thereof

    CN113583208A

  • Shape memory polyurethane material as well as preparation method and application thereof

    CN118440287A